2015
DOI: 10.1016/j.jcin.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Cerebral Embolization After Implantation of a Balloon-Expandable Aortic Valve Without Prior Balloon Valvuloplasty

Abstract: The implantation of a balloon-expandable aortic valve without versus with prior BAV, although performed with a shorter procedure time and lower contrast volume, is associated with a significantly higher volume of cerebral ischemic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 16 publications
7
64
2
Order By: Relevance
“…Among the studied populations, TAVI was performed without preimplantation BAV in 721 patients and with preimplantation BAV in 674 patients. The mean age was 81.3 years, and 49.6% of participants were female in 14 studies that reported both age and sex . The balloon‐expandable Edwards SAPIEN XT or SAPIEN 3 valve was implanted in 10 studies including 793 patients, and the self‐expandable Medtronic CoreValve was used in 7 studies including 602 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studied populations, TAVI was performed without preimplantation BAV in 721 patients and with preimplantation BAV in 674 patients. The mean age was 81.3 years, and 49.6% of participants were female in 14 studies that reported both age and sex . The balloon‐expandable Edwards SAPIEN XT or SAPIEN 3 valve was implanted in 10 studies including 793 patients, and the self‐expandable Medtronic CoreValve was used in 7 studies including 602 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The crude incidence of residual moderate or severe aortic regurgitation or PVL was reported in 9 studies and occurred in 16% (124 of 757) of patients. In this regard, 4 studies used the balloon‐expandable valve with a 3% rate (9 of 262 patients), and 5 studies used the self‐expandable valve with a 23% rate (115 of 495 patients). Of note, the need for postimplantation postdilation was reported in 14 studies and occurred in 18% (210 of 1177) of patients; 9 studies used the balloon‐expandable valve with a 14% rate (118 of 864 patients), and 6 studies used the self‐expandable valve with a 29% rate (92 of 313 patients).…”
Section: Resultsmentioning
confidence: 99%
“…The relatively large proportion of patients treated with direct valve implantation may represent the process of simplifying the TAVI procedure to increase its safety, but more evidence for such an approach is needed [21]. In fact, 33% of Polish centres perform aortic valvuloplasty during TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…9 In our study, the need for 11 This is also supported by a recent study showing a higher volume of cerebral ischemic lesions by diffusion-weighted magnetic resonance imaging in patients undergoing direct-TAVR in relation to patients undergoing TAVR with BAVP. 12 Furthermore, preparing the aortic valve with BAVP, especially in those patients with a larger burden of valve calcification, may offer more room and further decrease the risks of hemodynamic instability during device delivery, facilitating the proper position of the THV, potentially leading to a more precise deployment with better outcomes. [13][14][15] In addition, preparation of the aortic valve could facilitate full and symmetrical expansion of the device, ultimately resulting in less paravalvular leak and minimal transaortic gradient.…”
Section: Discussionmentioning
confidence: 99%